Pengaruh Iklim Organisasi dan Kepemimpinan Transformasional Terhadap Peningkatan Kinerja Guru Sekolah Minggu Buddha di Kota Denpasar - Ida Bagus Dharmika; Prita Puspita; Adriana Venny Ariani; Narti Narti; Ni Ketut Surya Sriadi (Institut Nalanda, 2022)
The purpose of this study was to determine the effect of organizational climate and transformational leadership on the performance of Buddhist Sunday School teachers in Denpasar City. This research uses multiple regression analysis. In this study using a sample using probability sampling technique, with a total sample of 85 respondents. This research uses primary data, data is collected by distributing questionnaires to respondents via google form which is tested with SPSS 20.0 for Windows. The results showed that organizational climate had a positive effect on the performance of Buddhist Sunday School teachers in Denpasar City with a correlation coefficient score (ry1 = 0.517) and a determination coefficient of the resulting score of r2y1 = 0.267. Transformational leadership has a positive effect on the performance of Buddhist Sunday School teachers in Denpasar City with the resulting correlation coefficient of ry2 = 0.833 and a coefficient of determination score (r2y2 = 0.694). Organizational climate and transformational leadership have a positive and significant effect on the performance of Buddhist Sunday School teachers in Denpasar City with the resulting correlation coefficient of ry1,2 = 0,856 and the coefficient of determination of the score (r2y1,2 = 0,733). Regression equation: 12 = 39.400 + 0.144X1 + 0.526X2. So for optimizing performance, it is necessary to have policies and regulations to improve organizational climate and transformational leadership.